Involvement of Different CD4+ T Cell Subsets Producing Granzyme B in the Immune Response to Leishmania major Antigens - Ikbel Naouar; Thouraya Boussoffara; Melika Ben Ahmed; Nabil Belhaj Hmida; Adel Gharbi; Sami Gritli; Afif Ben Salah; Hechmi Louzir (Mediators of Inflammation)
The nature of effector cells and the potential immunogenicity of Leishmania major excreted/secreted proteins (LmES) were evaluated using peripheral blood mononuclear cells (PBMCs) from healed zoonotic cutaneous leishmaniasis individuals (HZCL) and healthy controls (HC). First, we found that PBMCs from HZCL individuals proliferate and produce high levels of IFN-γ and granzyme B (GrB), used as a marker of activated cytotoxic T cells, in response to the parasite antigens. IFN-γ is produced by CD4+ T cells, but unexpectedly GrB is also produced by CD4+ T cells in response to stimulation with LmES, which were found to be as effective as soluble Leishmania antigens to induce proliferation and cytokine production by PBMCs from immune individuals. To address the question of regulatory T cell (Tregs) involvement, the frequency of circulating Tregs was assessed and found to be higher in HZCL individuals compared to that of HC. Furthermore, both CD4+CD25+ and CD4+CD25− T cells, purified from HZCL individuals, produced IFN-γ and GrB when stimulated with LmES. Additional experiments showed that CD4+CD25+CD127dim/- Tregs were involved in GrB production. Collectively, our data indicate that LmES are immunogenic in humans and emphasize the involvement of CD4+ T cells including activated and regulatory T cells in the immune response against parasite antigens.